Value Chain Marketing : A Marketing Strategy to Overcome Immediate Customer Innovation Resistance - Hintze, Stephanie (Contributions to Management Science,, 2015)
Value Chain Marketing (VCM) is a promising strategy to overcome immediate customers' innovation resistance. By pursuing VCM, material suppliers enlarge their target group beyond their immediate customers and address their downstream customers as well. Treading on relatively unexplored grounds, this book explores the relevance of VCM and comprehends its process; identifies the critical factors for suppliers' marketing success, and compares the performance of VCM trials, using a multi-method design linking case study research and computational modeling.